Bisnis Pariwisata Halal Bagi Keluarga Muslim Di Indonesia Dalam Perspektif Maqashid Al-Syari’ah - Al Kautsar, Izzy (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2022)
The tourism sector based on Islamic values ​​or called halal tourism is a new breakthrough. This sector is projected to be a method and way for Muslim travelers to travel. This is based on the tourism sector which will not run out of time due to the flexible nature of the tourism industry. Consumer protection. This study uses a normative research method with a statutory and conceptual approach. The results of this study are; 1) consumption preferences tend to benefit and harm the goods and services consumed so that goods that are beneficial are preferred over those that have no benefits and those that are harmful need to be avoided or far away do not need to be used as consumption choices in the family. 2) The concept of sharia tourism contains proper morals and character, represented by Islamic values ​​from sharia tourism products and services, in carrying out tourist trips not only aiming to enjoy the occasion but must be based on 5 things, including; efforts to protect religion, efforts to protect intelligence and reason, efforts to protect life, protection of wealth; and protection for offspring. 3) The Consumer Protection Law is an alternative law that practically seeks to protect the rights of tourists including the implementation of Islamic teachings, product and service safety, product and service clarity, choice of needs, and state guarantees in order to obtain sharia tourism products and services in accordance with the provisions principles of sharia tourism implementation.